Polar‐Group Activated Isospecific Coordination Polymerization of ortho‐Methoxystyrene: Effects of Central Metals and Ligands. Issue 8 (14th January 2019) - Chai, Yunjie; Wang, Lingfang; Liu, Dongtao; Wang, Zichuan; Run, Mingtao; Cui, Dongmei
Abstract: Stereoselective polymerization of polar vinyl monomers has been a long‐standing challenge because the employed transition‐metal catalysts are easily poisoned by polar groups of monomers. In this contribution, a series of β ‐diketiminato rare‐earth metal complexes 1 –5 (L 1–5 Ln(CH2 SiMe3 )2 (THF) n, Ln=Gd–Lu, Y, and Sc) were successfully synthesized. In combination with Al i Bu3 and [Ph3 C][B(C6 F5 )4 ], complexes 1 c (Tb)–1 g (Tm) exhibited high activities and excellent isoselectivities for the polymerization of ortho ‐methoxystyrene ( o MOS), in which, the polar methoxy group of o MOS did not poison but activated the polymerization through σ–π chelation to the active species together with the vinyl group. Moreover, the large Gd‐attached precursor 1 b showed a higher activity, albeit with a slightly decreased isoselectivity. The small Sc‐attached precursor 1 i was completely inert. Meanwhile, the spatial steric arrangement and the coordination mode of the β ‐diketiminato ligand could clearly affect and even block o MOS polymerization. This work sheds new light on the coordination polymerization of polar monomers. Abstract : Put on repeat : Self‐activated coordination‐insertion polymerization of polar ortho ‐methoxystyrene has been achieved by using cationic β ‐diketiminato rare‐earth metal catalysts in high activity and excellent isoselectivity ( mmmm >99 %; see figure). Moreover, the larger the metal is, the higher the catalytic activity is; in contrast, the central metal type had little effect on the selectivity except for the large Gd.